2011
DOI: 10.1039/c0cc04667a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and incorporation of a furan-modified adenosine building block for DNA interstrand crosslinking

Abstract: 2 0 -O-(3-(Furan-2-yl)propyl)adenosine was synthesized and evaluated for interstrand crosslink (ICL) formation in DNA duplexes. In situ oxidation of the furan moiety with NIS showed rapid crosslink formation to dA and dC, while dT and dG were inactive.Oligonucleotides that form interstrand crosslinks (ICLs) have found widespread applications in chemical biology research areas. Therefore, chemical and enzymatic methods have been developed to incorporate crosslinks into helical regions of DNA and RNA. 1 Examples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…On the other hand, the internally modified acpcPNA could only form the ICL when an unpaired nucleobase was available to react with the activated furan moiety, as in the case of the DNA target carrying a C‐insertion close to the furan modification site, despite the low duplex stability. The results are in good agreement with other studies on furan‐modified DNA probes, whereby the crosslinking efficiency was low when the target nucleobase was involved in base pairing [19,20] . However, the effect is more exaggerated in the case of PNA‐DNA duplexes since acpcPNA binds to DNA much more strongly than normal DNA.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…On the other hand, the internally modified acpcPNA could only form the ICL when an unpaired nucleobase was available to react with the activated furan moiety, as in the case of the DNA target carrying a C‐insertion close to the furan modification site, despite the low duplex stability. The results are in good agreement with other studies on furan‐modified DNA probes, whereby the crosslinking efficiency was low when the target nucleobase was involved in base pairing [19,20] . However, the effect is more exaggerated in the case of PNA‐DNA duplexes since acpcPNA binds to DNA much more strongly than normal DNA.…”
Section: Discussionsupporting
confidence: 90%
“…According to a previous study by Madder, [20] cytosine was found to be the most susceptible nucleobase for the ICL by furan‐modified DNA. To investigate the effect of switching of the probe from DNA to acpcPNA, we performed a preliminary crosslinking experiment between the terminally furan‐modified PNA(T) and its complementary DNA (DNA−com).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…In view of the general stability of the furan moiety before oxidation, handling during synthesis and binding events is straightforward and no special protection strategies or precautions need to be considered. This has led to the synthesis and evaluation of several alternative furan‐modified ODNs, allowing the fine‐tuning of yield and selectivity (Halila et al, ; Stevens and Madder, ; Jawalekar et al, ; Op de Beeck and Madder, , ; Stevens et al, ).…”
Section: Commentarymentioning
confidence: 99%